Beyond the numbers game: understanding organizational response to nationalization policy in the Middle East - Tahniyath Fatima (16500229) (2025)
Despite its potential benefits, the impact of nationalization initiatives that focus on developing the national workforce, such as Qatarization, on organizational performance remains largely elusive. Drawing from 313 responses from organizations in Qatar, this study illuminates these dynamics by investigating the associations between Qatarization as an indicator of HRM development, namely Qatarization effectiveness, and Qatarization as a statistical indicator, labeled as Qatari Employment Metric that measures higher proportion of Qatari staff, with organizational performance (both financial and non-financial). Our findings provide empirical support for the human capital theory and resource-based view theory through disclosing that Qatarization effectiveness has a positive impact on both financial and non-financial performance. However, a higher proportion of Qatari staff by itself does not necessarily signal better performance and may, in fact, negatively influence non-financial outcomes. We further examine the complex institutional context and discover that stakeholder uncertainty attenuates the positive effect of Qatarization effectiveness on non-financial performance, while the presence of Qatarization expertise can counterbalance the adverse impact of high percentage of Qatari staff on non-financial performance. The results enhance our understanding of the complexities of nationalization public policies and their bearing on organizational performance in the Middle East, thereby emphasizing the necessity of strategic human resource management practices for effective human capital policy implementation. Other Information Published in: Journal of International Management License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.intman.2025.101272